Pengaruh media pembelajaran berbasis 3D dan animasi molekul dengan kooperatif tipe savi terhadap hasil belajar kimia siswa SMA kelas X pada materi larutan elektrolit dan non elektrolit - Hia, Erlin Karya Kasih; Harahap, Annisa Sabbillah; Nugraha, Asep Wahyu (Educenter : Jurnal Ilmiah Pendidikan, 2022)
The purpose of this study was to determine the effect of 3D-based learning media and molecular animation with SAVI cooperative type on the chemistry learning outcomes of high school students in class X on the subject of electrolyte and non-electrolyte solutions. This research was conducted at SMAN 1 Sunggal school. The stages of this research are: 1) giving the pre-test at the beginning, 2) the learning process, and 3) giving the post-test. The instruments used in this study were in the form of tests and questionnaires. The results showed that 3D-based learning media and molecular animation could improve student learning outcomes in electrolyte and non-electrolyte solutions. The results of the percentage of student responses to 3D-based learning media and molecular animations are 92.42% which is categorized as very feasible to be applied to the learning process of electrolyte and non-electrolyte solutions.